(untitled) (Research, Society and Development, 2025)
Obesity is a complex chronic condition characterized by excessive body fat accumulation, posing significant clinical management challenges due to its multifactorial nature. GLP-1 receptor agonists emerge as a promising therapeutic option for obesity treatment. This study aims to evaluate the efficacy and safety of these agonists, analyzing their clinical implications across different patient profiles. Using the PICO strategy, an integrative review was conducted, selecting five articles from PubMed, SciELO, and Cochrane Library databases, covering the period from 2019 to 2024. Inclusion criteria considered studies in Portuguese and English, available in full, directly addressing the topic. Excluded were studies unavailable in full, case studies, and experience reports not directly related to the topic. Results indicate that GLP-1 agonists, such as semaglutide and liraglutide, are effective in weight reduction and offer additional benefits in obesity management. However, their use should be personalized, considering individual patient characteristics to optimize outcomes and minimize adverse effects. It is concluded that GLP-1 agonists are effective across a wide range of patient profiles, from those with severe obesity to individuals with obesity associated with other chronic conditions. Furthermore, obesity management requires a comprehensive approach combining pharmacological therapy with lifestyle interventions, such as diet and physical exercise, along with continuous monitoring to ensure treatment safety and efficacy.